Nasal Transmissible Venereal Tumor (TVT) in Dogs - Conte, Fernanda; Strack, Adriane; Bastos-Pereira, Amanda Leite; Pereira, Marcy Lancia (Acta Scientiae Veterinariae, 2022)
Background: Transmissible venereal tumors (TVT) are naturally occurring neoplasms that can be transmitted through copulation or cell transplantation. It is a disease that affects canines, has no preference for sex or breed, and generally noticed in the external genital apparatus. Extragenital occurrence may eventually be seen; however, nasal involvement has been described in only a few reports of studies conducted in Brazil. Therefore, the objective of this study is to report 3 cases of nasal TVT in dogs who were treated in 2 municipalities in the mountainous region of Santa Catarina, Brazil. Cases: This case report includes 3 male mixed-breed canines of age 3-13. Only 1 of the animals was castrated. As per the medical history, some points, such as an enlarged nasal region, sneezing, nasal discharge, and hoarseness, reported by the dogs’ respective owners were similar among all the dogs. Likewise, nosebleed was observed on physical examination in all the cases. The result of cytological examination was inconclusive only in 1 case. Rhinoscopy, incisional biopsy, and histopathological examination were then performed for achieving a definitive diagnosis. In the 2 cases wherein cytology gave conclusive results, the cytological smears showed changes suggestive of TVT, such as cells with eccentric nuclei and little cytoplasm, which had vacuoles inside them. In 2 cases, radiographic examinations of the skull were also performed. The images showed changes in bone radiopacity, conformation of trabeculae with areas of bone lysis and cell proliferation, and irregularity in the contour of the nasal bone. After TVT diagnosis was confirmed, chemotherapy was initiated using vincristine at a dose of 0.75 mg/m2 for 2 cases and 0.025 mg/kg for the remaining case. The number of chemotherapy sessions and duration of treatment until the resolution of lesions and clinical signs varied as per the differences in the patients’ blood counts performed prior to each session. Discussion: TVT occurs between 1 and 7 years of life. It occurs more frequently in sexually active animals and has no preference for breed. Of the 3 cases reported herein, only one of the patients was elderly. All the patients were male mixed-breed dogs, and only 1 of them was castrated. The implantation of neoplastic cells through natural mounts, licks, scratches, or bites of affected areas are the most widely accepted reasons for the transmission of this neoplasm. With regard to the nasal presentation described in the present report, it is hypothesized that the smelling or licking of the neoplastic areas by the animal may favor cell implantation, leading to the subsequent development of a tumor. Nasal TVT should be considered as a differential diagnosis for dogs with chronic symptoms of the upper respiratory tract, such as increased local volume, nasal discharge, nosebleed, and sneezing. These signs are consistent with those described in this report. Radiographic evaluation was performed in 2 cases and both showed changes in bone radiopacity and trabeculae conformation, in addition to areas of bone lysis and cell proliferation, which are common in neoplastic processes. A presumptive diagnosis can be achieved from the medical history, clinical signs, and physical examination. Cytological and histopathological examination are the confirmatory methods; however, it is used less frequently and especially when cytological evaluation does not provide a definitive diagnosis. Antineoplastic chemotherapy with vincristine is the first-choice treatment protocol, which also proved to be effective for the patients in this report. Although TVT commonly affects the external genitalia of dogs, in the cases reported herein, it was located exclusively in the nasal region. Keywords: TVT, dog, nasal, vincristine. Título: Tumor venéreo transmissível (TVT) nasal em cães Descritores: TVT, cão, nasal, vincristine.